South African economic policy under democracy - Aron, Janine; Kahn, Brian, 1953-; Kingdon, Geeta Gandhi (Oxford : Oxford University Press, 2009)
South Africa experienced a momentous change of government from the Apartheid regime to its first democratic government in 1994. This text provides an up-to-date and comprehensive assessment of South Africa's economic policies and performance under democracy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: South Africa -- Economic policy; South Africa -- Economic conditions -- 1991-